Analysis of the healthy food market in the Russian Federation and the Republic of Adygea - G. V. Karamushko; Z. N. Khatko; N. Kh. Navasardyan (Новые технологии, 2021)
The goal. Marketing research and analysis of the current situation on the Russian healthy food market in general and the Republic of Adygea in particular. The methods. The results of desk research carried out by the authors, methods of generalization, comparative analysis, induction, decomposition, graphical method were used. The Results. The article outlines the results of the analysis of the public catering market in Russia in general, and the Republic of Adygea, in particular. Despite the crisis in the economy, the Russian public catering market is quite promising. The capacity of domestic catering is several times higher than the current turnover, which indicates its undersaturation. In addition, the article presents monitoring of the Russian and regional market for healthy food products, which led to the conclusion that public catering networks promoting a healthy lifestyle are recognized as one of the fastest growing segments of the public catering market. The conclusion. The growth of the Russian and world markets for healthy food is a direct consequence of changes in consumer patterns. Today traditional criteria of consumer choice in the food market (price, taste and quality) are inseparable from a new group of criteria, most of which are indicators of growing popularity for residents of all countries: health and a healthy lifestyle, safety and transparency (consumers want to know what exactly they consume). A healthy lifestyle today is becoming not just a trend, but a lifestyle all over the world.